2019
DOI: 10.1002/jcp.28118
|View full text |Cite
|
Sign up to set email alerts
|

LINC00520 targeting miR‐27b‐3p regulates OSMR expression level to promote acute kidney injury development through the PI3K/AKT signaling pathway

Abstract: Background Acute kidney injury (AKI) shows several kinds of disorders, which acutely harm the kidney. However, the current medical methods have limited therapeutic effects. The present study aimed to find out the molecular mechanism of AKI pathogenesis, which may provide new insights for future therapy. Methods Bioinformatic analysis was conducted using the R language (AT&T BellLaboratories, University of Auckland, New Zealand) to acquire the differentially expressed long noncoding RNAs (lncRNAs) and messenger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 42 publications
1
48
0
Order By: Relevance
“…It was recently discovered that lncRNAs functioned as miRNA sponges. Tian's study indicated that lncRNA LINC00520 acted as a ceRNA to competitively inhibit miR-27b-3p during I/R injury 16 . Negative regulation between miR-21 and GAS5 was first found in breast tumors 12 .…”
Section: Discussionmentioning
confidence: 99%
“…It was recently discovered that lncRNAs functioned as miRNA sponges. Tian's study indicated that lncRNA LINC00520 acted as a ceRNA to competitively inhibit miR-27b-3p during I/R injury 16 . Negative regulation between miR-21 and GAS5 was first found in breast tumors 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Pi3K/akt/mTor is a crucial signaling pathway involved in the carcinogenicity and tumorigenesis of different cancer types, and is closely related to cell biological functions, such as energy metabolism, proliferation, apoptosis and cell invasion (16)(17)(18)(19). Previous studies have revealed that certain mrnas are co-expressed with cYP2e1 and participate in the Pi3K/akt/mTor signaling pathway (20,21).…”
Section: Cyp2e1 Regulates Key Pi3k/akt/mtor Signaling Proteinsmentioning
confidence: 99%
“…Increasing evidences suggest miRNAs play a crucial role in occurrence and development of diseases. For renal I/R injury, miRNAs play an important role in different aspects, such as apoptosis and inflammation [18,19]. Xie et al reported that miR-128-3p improved the acute kidney injury via inhibiting cell apoptosis [18].…”
Section: Discussionmentioning
confidence: 99%